아동용 과자제품의 한글브랜드디자인(레터링) 이미지에 대한 연구 - 김명혜; Kim Myung Hye; 한창호; Han Chang Ho (기초조형학연구, 2018)
생활 속에서 자주 접하는 국내 과자브랜드명은 외래어와 혼합어로 이루어진 이름의 비중이 큰 반면에 한글로 표기된 브랜드레터링이 주를 이룬다. 과자브랜드 한글레터링은 주로 정형화되지 않은 자유분방한 표현이 많아 소비자에게는 친근한 이미지로 각인된다. 본 연구는 과자브랜드 한글레터링이 아동에게 어떤 감성으로 보여 지는 지에 대해 알아보고자 감성언어를 직접 채집하여 분류해 보는데 목적이 있다. 연구 대상은 국내 5대 제과회사의 홈페이지에 중요하게 소개된 제품들 위주로 70개 제품을 선정하였다. 과자의 주 소비층인 초등학생 1, 3, 6학년 다양한 연령의 아동 72명이 과자브랜드 한글레터링을 본 후에 반응한 94개 단어를 비슷한 특성끼리 모아 5개 그룹으로 나누었다. <1그룹>은 형상연상형 감성 반응, <2그룹>은 구상연상형 감성 반응, <3그룹>은 추상연상형 감성 반응, <4그룹>은 감정이입형 감성 반응, <5그룹>은 수반감각형 감성 반응 그룹이다. 또한, 과자브랜드 한글레터링 형태를 세 가지로 분류 하였다. 첫째, 그래픽 프리핸드 레터링으로 매우 자유롭고 과감한 레터링 형태이며 대상 전체에서 차지하는 비중이 제일 많았다. 둘째, 캘리그래피형으로서 붓의 필력을 사용해 전통적 느낌이 강한 레터링이다. 셋째, 기존 개발 폰트를 기본으로 변화가 크지 않은 타입페이스형 레터링으로 분류할 수 있다. 아동은 과자브랜드 한글레터링을 단순한 문자로만 보지 않고 활발한 연상반응을 통해 감성언어를 생성했는데 그 중 추상연상형 감성 반응이 가장 많았다. 과자브랜드 레터링에서 채집된 감성언어를 참고로 아동의 감성에 내포되어 있는 특성을 면밀하고 섬세하게 관찰한다면 그 결과로 아동을 위한 디자인 개발에 적절히 적용할 수 있을 것으로 판단된다. While domestic confectionery brand names frequently seen in daily life are mostly composed of combination of foreign and Korean words, the brand letters are mostly written in Korean. Korean alphabet lettering of confectionery brands has many unstandardized and random expressions, providing a familiar image to consumers. The purpose of this study is to research what sensitivity children see from confectionery brands' Korean alphabet lettering by directly collecting and classifying sensitivity words. To accomplish the objects of this study, we selected 70 products among those that were importantly introduced in the websites of 5 biggest domestic confectionary companies. Total 72 children from various age groups of 1st graders, 3rd graders and 6th graders, who are main targets of confectionery products, were asked to see confectionary brand Korean alphabet lettering, and 94 words that the children reacted with were classified into 5 groups of similar characteristics. Group 1 was figure associating reaction, Group 2 was design associating reaction, Group 3 was abstract associating reaction, Group 4 was empathy reaction, and Group 5 was involved with sense reaction. In addition, the types of confectionery brand Korean alphabet lettering were divided into three categories. The first category was graphic free-hand lettering, which was a very free and bold lettering type and had the biggest portion in the whole objects. The second category was a caligraphy type, which was the lettering that had strong traditional feeling with the use of power of brush strokes. The third category was a typeface type lettering that hardly had changes based on the existing fonts. The children created sensitivity words through active associative reactions rather than viewing Korean alphabet lettering as simple letters. If the characteristics implicit in children's sensitivity are observed meticulously and minutely with reference to the sensitivity words collected from the confectionery brand lettering, the result of the observation can be properly used for development of designs for children.